A Comparison Study on the Rhetorical Structures of Abstracts in Two Disciplines Indexed Journals - Nurhayati S.; Fadilah (International Journal of English and Applied Linguistics (IJEAL), 2024)
Abstracts offer a concise summary of a study, helping readers determine whether to read the full article, as they serve as the initial point of access to knowledge and are among the first freely available "mini-texts" online (Huckin, 2001). This study aimed to compare the rhetorical structures and their occurrence in abstracts from IT journals and Language, Literature, and Education (LLE) journals, as well as to assess how well writers adhere to abstract writing guidelines. The study analyzed 60 abstracts—30 from each journal type—using Hyland’s (2000) model. The analysis revealed 19 different move structures, with six abstracts following the same patterns and 13 displaying varied structures. The most common move structures were M1-M2-M3-M4-M5 and M1-M2-M3-M4. There were instances of merging and repetition in moves 2 and 3, and the average awareness of using all move structures was higher in LLE (93%) compared to IT abstracts (87%). Hyland's (2000) five-move model provides a framework for maintaining consistency in abstract organization by emphasizing the significance and order of each move. The study found that certain structures included repetitive or cyclical moves, indicating the importance of offering clear textual guidance on the correct sequence.